Primary mucinous carcinoma of the axillary skin: a case report & the role of adjuvant tamoxifen - Nur Fa’izah Ab Muin,; Fuad I, (Penerbit UKM, 2024)
Primary mucinous carcinoma of the skin (PMCS) is a rare cancer. It is indolent and progresses slowly but can recur locally, damaging the structure. The majority of mucinous carcinoma that occurs in the skin are metastatic lesions originating from various sites. In terms of morphology, PMCS is almost indistinguishable from secondary metastatic deposits. We reported a case of a 44-year-old male with left axillary skin PMCS that had spread to axillary lymph nodes. The pathologic diagnosis was challenging but was facilitated by expert pathologists from different centers. A multidisciplinary meeting concluded that the best management approach was to include a wide local excision and axillary clearance followed by adjuvant tamoxifen. The role of adjuvant radiotherapy was discussed but was declined by the patient. The patient is well now with no recurrence, 22 months since the diagnosis.